Homogenous dose prescription in Gamma Knife Radiotherapy: combining the best of both worlds - Spaniol, Manon; Abo-Madyan, Yasser; Ruder, Arne Mathias; Fleckenstein, Jens; Giordano, Frank Anton; Stieler, Florian (Physica medica, 2024)
PURPOSE: Stereotactic radiosurgery with linear accelerators (LINACs) or Leksell Gamma Knife® (LGK, Elekta AB) is an established treatment option for intracranial tumors. When those are involving/abutting organs at risk (OAR), homogenous and normofractionated treatments outmatch single fraction deliveries. In such situations, it would be desirable to balance LINAC's homogeneity benefits with LGK's dose gradient attributes. In this study, we determined homogeneity and OAR sparing ranges using a non-clinical, homogenous prototype version of LGK Lightning. - METHODS: We retrospectively analyzed thirty fractionated LGK Icon in-house patients with acoustic neuromas, pituitary adenomas and meningiomas. Four treatment plans were generated (54 Gy,1.8 Gy/fx) per patient: one LINAC plan, one clinical Lightning plan ("LGK") and two prototype Lightning plans ("LGK Hom" and "LGK OAR"). We analyzed Dmean and D2% for different OAR, Gradient Index (GI), Paddick Conformity Index (PCI), Homogeneity Index (HI) and beam-on-time (BOT). - RESULTS: While the LINAC vs. Lightning plans (LGK Hom|LGK OAR|LGK) boast better homogeneity (median: 1.08 vs. 1.18|1.24|1.35) and shorter BOT (median: 137 s vs. 432 s|510 s|510 s), Lightning plans show improved GI (median: 6.68 vs. 3.86|3.50|3.19), similar PCI (median: 0.75 vs. 0.76|0.75|0.82) and significantly reduced OAR doses. For in-tumor OAR, LGK Hom and LINAC plans achieves similar OAR sparing with improved GI for LGK Hom. - CONCLUSIONS: This study is a preliminary attempt to combine the dosimetric advantages of LINAC and LGK treatment planning. We observed that LGK plan homogeneity can be improved toward LINAC standards while maintaining the LGK advantage of favorable OAR doses and GI. Additionally, in-tumor OAR hotspots can be considerably reduced.
Online veröffentlicht: 29 December 2023
Gesehen am 04.07.2024